2016
DOI: 10.4103/0377-4929.188108
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of plasmid-mediated quinolone resistance in Gram-negative bacteria from a tertiary hospital in Nigeria

Abstract: This study further confirms high level resistance to many antimicrobials in different species of Gram-negative bacteria including fluoroquinolones and spread of PMQR genes in Southern Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Regional FQR rates were 23.5% in North America, 29.4% in Europe, 33.2% in Asia, 38.7% in Latin America, and 25.5% in the South Pacific (32). Studies across Nigeria also reported various degree of FQR up to 50% which is almost comparable to the present study (33)(34)(35). Over the counter use of these drugs in Nigeria has probably led to such low degree of sensitivity of uropathogens to this drug.…”
Section: Discussionsupporting
confidence: 87%
“…Regional FQR rates were 23.5% in North America, 29.4% in Europe, 33.2% in Asia, 38.7% in Latin America, and 25.5% in the South Pacific (32). Studies across Nigeria also reported various degree of FQR up to 50% which is almost comparable to the present study (33)(34)(35). Over the counter use of these drugs in Nigeria has probably led to such low degree of sensitivity of uropathogens to this drug.…”
Section: Discussionsupporting
confidence: 87%
“…This is similar to ndings from studies done across regions in sub-sahara Africa which also found a high prevalence of PMQR determinants among quinolone resistant organisms with e ux pumps and drug-modyfying mechanisms being more common than target protection mechanism. 21 The few studies available on PMQR in Nigeria have also shown a high prevalence of the e ux and drug modifying genes in clinical isolates from humans, 14,16,21,29 also contrary to earlier reports and distribution of target site protection, drug-modifying and e ux determinants are rather of greater signi cance. Studies done outside the continent also showed a high prevalence of PMQR in clinical isolates.…”
Section: Discussionmentioning
confidence: 92%
“…13 More recently, there are reports of high level resistance to quinolones in Nigeria as well as neighbouring countries in West Africa. [13][14][15][16][17][18][19][20] Though, target protection mechanism (qnr proteins) were the rst to be discovered, previous studies suggested aac(6′)-Ib-cr to be the commonest PMQR gene followed by qepA and the qnr genes 11,14 and a more recent systematic review of published articles on uoroquinoloneresistant enteric bacteria in sub-Saharan Africa found a high prevalence of PMQR genes as well as an upregulation in e ux pumps and also the drug-modifying mechanism across several species of bacteria. 21 In view of the need for continuous antimicrobial resistance surveillance as part of global efforts to contain the emergence and dissemination of antimicrobial resistance, we determined the distribution of PMQR genes in Gram negative bacilli from a tertiary healthcare institution in South-West Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…13 More recently, there are reports of high level resistance to quinolones in Nigeria as well as neighbouring countries in West Africa. [13][14][15][16][17][18][19][20] Though, target protection mechanism (qnr proteins) were the rst to be discovered, previous studies suggested aac(6′)-Ib-cr to be the commonest PMQR gene followed by qepA and the qnr genes 11,14 and a more recent systematic review of published articles on uoroquinoloneresistant enteric bacteria in sub-Saharan Africa found a high prevalence of PMQR genes as well as an upregulation in e ux pumps and also the drug-modifying mechanism across several species of bacteria. 21 In view of the need for continuous antimicrobial resistance surveillance as part of global efforts to contain the emergence and dissemination of antimicrobial resistance, we determined the distribution of PMQR genes in Gram negative bacilli from a tertiary healthcare institution in South-West Nigeria.…”
Section: Introductionmentioning
confidence: 99%